Analisis Pola Distribusi Spasial Sarana Ekonomi di Desa Je’nemadinging Kabupaten Gowa - Andi Fatimah; Abdul Malik; Maddatuang M; Uca Sideng; Amal Arfan (LaGeografia, 2023)
The availability of geospatial information presented in the form of map visualizations related to the distribution and spatial distribution patterns of economic facilities of a village is an important need to support village development. This study aims to map the distribution and spatial distribution patterns of economic facilities in Je’nemadinging Village based on geospatial information by providing a village database including the distribution of general economic facilities in one village, the distribution of economic facilities based on population, the distribution of economic facilities based on roads, and spatial distribution patterns of village economic facilities. Data collection in this study includes primary data collection in the form of plotting for economic facilities and secondary data for population data. Data analysis was carried out using the analysis of the nearest neighbor. The results of this study present a map of information and spatial data including a map of the distribution of economic facilities in general in one village, a map of the distribution of economic facilities based on population, a map of the distribution of economic facilities based on roads, spatial distribution patterns of village economic facilities, and an analysis of the relationship with the potential of villages in the future. This spatial data and information can be a reference in decision making in the context of village development.AbstrakKetersediaan informasi geospasial yang disajikan dalam bentuk visualisasi peta terkait sebaran dan pola distribusi spasial sarana ekonomi suatu desa merupakan kebutuhan penting guna mendukung pembangunan desa. Penelitian ini bertujuan untuk melakukan pemetaan sebaran dan pola distribusi spasial sarana ekonomi Desa Je’nemadinging yang berbasis informasi geospasial dengan penyediaan database desa meliputi sebaran sarana ekonomi secara umum pada satu desa, sebaran sarana ekonomi berdasarkan jumlah penduduk, sebaran sarana ekonomi berdasarkan jalan, dan pola distribusi spasial sarana ekonomi desa. Pengumpulan data dalam penelitian ini meliputi pengumpulan data primer berupa plotting untuk titik koortdinat sarana ekonomi dan data sekunder untuk data penduduk. Analisis data dilakukan menggunakan analisis tetangga terdekat (nearest neighbor). Hasil penelitian ini menyajikan peta informasi dan data spasia meliputi peta sebaran sarana ekonomi secara umum pada satu desa, peta sebaran sarana ekonomi berdasarkan jumlah penduduk, peta sebaran sarana ekonomi berdasarkan jalan, pola distribusi spasial sarana ekonomi desa, dan analisis keterkaitan dengan potensi desa kedepannya. Data dan informasi spasial ini dapat menjadi acuan dalam pengambilan keputusan dalam rangka pembangunan desa.